Toxina botulínica: compuestos emergentes en Chile - Moyano V., Álvaro; Leddihn B., Víctor (Revista Hospital Clínico Universidad de Chile, 2018)
Botulinum toxin A is a vastly used therapy for treatment or management of a variety of health conditions. We are talking about a biological compound which is nowadays manufactured by many different laboratories, with distinct and specific characteristics for each one of their products. Although research and use of this toxin have been worldwide established for many years , in Chile we have been using it for over twenty years and since then its uses have been expanding to many fields. During the last few years, new toxins from different laboratories have been incorporated to our country, being necessary to know about them, their similarities and differences as well as to be aware of the uses that are approved or not for each particular drug.